ASSESSING THE INFRINGEMENT OF WIDOWS’ RIGHTS DURING WIDOWHOOD RITES PRACTICES IN TALENSI AND NABDAM IN THE UPPER EAST REGION OF GHANA - Ba - an, Maxwell Tengolzor; Adjuri, Justine Abaguri; Bedzra, Linda; Segbefia, Samuel Kwabla (jfpublisher, 2022)
The purpose of this study was to investigate how widowhood rites practices infringe on the rights of widows in contemporary times in Talensi and Nabdam. One such practice includes the commodification and oppression of the weak, particularly through violations of widows' sexual and human rights. Participant observation, interviews, and community immersion were employed in the research. The study found that both ethnic groups practice widowhood rites during fresh and final burials. An ethnographic research design was adopted to explore the cultural aspects of widowhood rites in the Talensi and Nabdam districts. Inter-ethnic disparities in these practices were also uncovered. The findings revealed that widowhood rites are detrimental to the health and rights of widows. Widows are denied opportunities to exercise their rights and are instead subjected to strict instructions on what they can and cannot do. Additionally, the practice of forcing an inheritor on the widow perpetuates economic abuse by denying widows and their children the right to inherit the deceased's property. The study concluded that a rigorous examination of various cultural practices is necessary to eliminate factors that violate women's rights. For instance, the right to dignity should be critically assessed and, where necessary, amended. Since culture is dynamic, traditional practices should evolve over time. To address these issues effectively, the researcher recommends mobilizing older women as change agents, especially in Ghana and other underdeveloped countries where women's lives are heavily influenced by customary or traditional religious standards.